2007
DOI: 10.1212/01.wnl.0000250335.56958.f0
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic pain distorts visuospatial perception

Abstract: Spatial perception is achieved by integrating multisensory information. Using visual subjective body midline (vSM) judgments in patients with unilateral limb pain (complex regional pain syndrome [CRPS]), we found that their vSM deviated toward the affected side; however, deafferentation of the affected limb caused a transient pain decrease and a transient shift of the vSM deviation toward the unaffected side. Our results indicate that the persistent pain state in CRPS distorts visuospatial perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 10 publications
5
62
2
Order By: Relevance
“…the unilateral pain [36]. Neglect symptoms reduced after the application of nerve blocks, and a similar trend was shown in healthy participants [36].…”
Section: An Impaired Perception Of Space Not Limited To the Side Of Tsupporting
confidence: 60%
See 4 more Smart Citations
“…the unilateral pain [36]. Neglect symptoms reduced after the application of nerve blocks, and a similar trend was shown in healthy participants [36].…”
Section: An Impaired Perception Of Space Not Limited To the Side Of Tsupporting
confidence: 60%
“…After prism adaptation, visual body midline judgments erred in the opposite direct, towards the side of the unaffected side [35]. In contrast to previous studies [5][6][7]16,24,25,34], these latter experiments [35,36,38] demonstrated that the side for which there is a diminished representation of space does not always correspond to that of the affected limb.…”
Section: An Impaired Perception Of Space Not Limited To the Side Of Tmentioning
confidence: 57%
See 3 more Smart Citations